A versatile enhanced freeze-substitution protocol for volume electron microscopy - Bélanger, Sébastien; Berensmann, Heather; Baena, Valentina; Duncan, Keith; Meyers, Blake C.; Narayan, Kedar; Czymmek, Kirk J. (Frontiers in Cell and Developmental Biology, 2022)
Volume electron microscopy, a powerful approach to generate large three-dimensional cell and tissue volumes at electron microscopy resolutions, is rapidly becoming a routine tool for understanding fundamental and applied biological questions. One of the enabling factors for its adoption has been the development of conventional fixation protocols with improved heavy metal staining. However, freeze-substitution with solvent based fixation and staining has not realized the same level of benefit. Here, we report a straightforward approach using a 2% osmium tetroxide, acetone and 3%+ water substitution fluid (compatible with traditional or fast freeze-substitution protocols), warm-up to 0᧐C and transition from solvent to aqueous 2% OsO4. Once fully hydrated, samples were processed in aqueous based potassium permanganate, thiocarbohydrazide, osmium, uranium and lead acetate before resin infiltration and polymerization. We observed a consistent and substantial increase in heavy metal staining across diverse and difficult to fix test organisms and tissue types; including plant tissues, nematodes, yeast and bacteria. Our approach opens new possibilities to combine the benefits of cryo-preservation with volume electron microscopy in diverse organisms.